2019
DOI: 10.22434/ifamr2018.0069
|View full text |Cite
|
Sign up to set email alerts
|

Managing working capital efficiency in Turkish agribusinesses and the impact of globalization: insights from an emerging market

Abstract: The efficiency of working capital is a major determinant of firm profitability. So, the grasp of working capital dynamics is extremely important for managers, but also for policy makers, since inefficient working capital management is an important source of industrial sickness. This study focuses on the profitability impacts of working capital policies of Turkish agribusinesses, and aims to investigate the potential effects of globalization on these interrelated relationships. The findings obtained from pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While some authors have suggested the existence of a negative relationship (Aytac et al 2020;Fernández-López et al 2020;Sensini and Vazquez 2021), others have revealed a positive relationship (Lyroudi and Lazaridis 2000;Thapa 2013;Akdoğan and Dinç 2019), and some have suggested that there is no significant relationship between these two variables (Rey-Ares et al 2021). Nurein et al (2015) stated that there is an inverted U-shaped relationship between profitability and ccc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors have suggested the existence of a negative relationship (Aytac et al 2020;Fernández-López et al 2020;Sensini and Vazquez 2021), others have revealed a positive relationship (Lyroudi and Lazaridis 2000;Thapa 2013;Akdoğan and Dinç 2019), and some have suggested that there is no significant relationship between these two variables (Rey-Ares et al 2021). Nurein et al (2015) stated that there is an inverted U-shaped relationship between profitability and ccc.…”
mentioning
confidence: 99%
“…; Mabandla and Makoni 2019; Gołaś 2020; Rey-Ares et al 2021) (calculated as the current assets divided by current liabilities); salesgr -sales growth (Deloof 2003; García-Teruel and Martínez-Solano 2007; Ademola 2014; Pais and Gama 2015; Aytac et al 2020; Fernández-López et al 2020; Gołaś 2020) (calculated as the difference in total sales from the previous year); debtratio(Ademola 2014;Baños-Caballero et al 2014;Nurein et al 2015;Pais and Gama 2015;Akdoğan and Dinç 2019;Aytac et al 2020;Fernández- López et al 2020;Rey-Ares et al 2021;Sensini and Vazquez 2021…”
mentioning
confidence: 99%
“…All plans that would be carried out in the contract farming were prepared by involving PT Bloom Agro, Bangkit Merbabu Farmers Group and Extension Officers based on the capabilities of each party, both members of the Bangkit Merbabu Farmers Group and PT Bloom Agro. Akdogan & Dinc (2019) defines organizing as the whole process of grouping people, tools, tasks, responsibilities and authorities into a single unit in order to achieve a predetermined goal. The success of the contract farming in terms of organization is achieved because in the implementation of the contract farming, the production sector, quality control (QC) sector, packaging sector and product storage sector worked together to assist the smooth implementation of the contract farming.…”
Section: The Success Of Contract Farmingmentioning
confidence: 99%
“…The need for efficient WCM in both crisis and normal periods has been demonstrated in previous studies in developing countries [26,27]. Since China is among the few countries that had successfully control COVID-19, we aim to fill this gap by examining the WC-financial performance relationship in China's agri-food sector during both COVID-19 and the financial crisis of 2008.…”
Section: Introductionmentioning
confidence: 99%